2012
DOI: 10.1002/hyp.9435
|View full text |Cite
|
Sign up to set email alerts
|

Using selected pharmaceutical compounds as indicators for surface water and groundwater interaction in the hyporheic zone of a low permeability riverbank

Abstract: This study investigates the applicability of selected pharmaceutical compounds (e.g. sulfamethoxazole, carbamazepine, ibuprofen) as anthropogenic indicators for the interaction of surface water and groundwater in the hyporheic zone of an alluvial stream. Differences in transport behaviour and the resulting distribution of the pharmaceuticals in the riverine groundwater were evaluated. The investigated field site in the Grand Duchy of Luxembourg, Europe is represented by low permeable sediments and confined aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 46 publications
1
7
0
2
Order By: Relevance
“…5). It was previously found that sulfamethoxazole is mobile, only slightly degradable and therefore easily transported to groundwater (Banzhaf et al, 2012).…”
Section: Potential Transfer Of Pesticides and Pharmaceutical Compoundmentioning
confidence: 99%
“…5). It was previously found that sulfamethoxazole is mobile, only slightly degradable and therefore easily transported to groundwater (Banzhaf et al, 2012).…”
Section: Potential Transfer Of Pesticides and Pharmaceutical Compoundmentioning
confidence: 99%
“…Allen et al 2010;Banzhaf et al 2013;Boulton et al 1998;Krause et al 2009). Much less research has been carried out at the local or flood plain scale (Langhoff et al 2006, see also section 2.1.2).…”
Section: Coverage Of Groundwater-surface Water Interaction At the Regmentioning
confidence: 99%
“…Despite the known negative influence of these compounds on freshwater ecosystems such as toxicological effects on biological systems, they also can be used for scientific purposes: Persistent organic micropollutants may be suitable tracers to better understand and characterize hydrological processes (Clara et al, 2004). Organic micropollutant concentrations (sulfamethoxazole, carbamazepine, ibuprofen) were used as anthropogenic indicators in the hyporheic zone (Banzhaf, Krein, & Scheytt, 2012) and to understand GW–SW interactions in a lowland Chalk catchment (Manamsa, Lapworth, & Stuart, 2016). A prominent example is carbamazepine which is often considered conservative due to its long half‐life compared to the travel time of river water (Guillet et al, 2019; Kunkel & Radke, 2012; Pal, Gin, Lin, & Reinhard, 2010; Schwientek, Guillet, Rügner, Kuch, & Grathwohl, 2016).…”
Section: Introductionmentioning
confidence: 99%